Patients' perspectives on quality and patient safety failures: lessons learned from an inquiry into transvaginal mesh in Australia - Mina Motamedi; Chris Degeling; Stacy M. Carter (BMC, 2024)
Abstract Background Transvaginal mesh (TVM) surgeries emerged as an innovative treatment for stress urine incontinency and/or pelvic organ prolapse in 1996. Years after rapid adoption of these surgeries into practice, they are a key example of worldwide failure of healthcare quality and patient safety. The prevalence of TVM-associated harms eventually prompted action globally, including an Australian Commonwealth Government Senate Inquiry in 2017. Method We analysed 425 submissions made by women (n = 417) and their advocates (n = 8) to the Australian Senate Inquiry, and documents from 5 public hearings, using deductive and inductive coding, categorisation and thematic analysis informed by three 'linked dilemmas' from healthcare quality and safety theory. We focused on women's accounts of: a) how harms arose from TVM procedures, and b) micro, meso and macro factors that contributed to their experience. Our aim was to explain, from a patient perspective, how these harms persisted in Australian healthcare, and to identify mechanisms at micro, meso and macro levels explaining quality and safety system failure. Results Our findings suggest three mechanisms explaining quality and safety failure: 1. Individual clinicians could ignore cases of TVM injury or define them as 'non-preventable'; 2. Women could not go beyond their treating clinicians to participate in defining and governing quality and safety; and. 3. Health services set thresholds for concern based on proportion of cases harmed, not absolute number or severity of harms. Conclusion We argue that privileging clinical perspectives over patient perspectives in evaluating TVM outcomes allowed micro-level actors to dismiss women's lived experience, such that women's accounts of harms had insufficient or no weight at meso and macro levels. Establishing system-wide expectations regarding responsiveness to patients, and communication of patient reported outcomes in evaluation of healthcare delivery, may help prevent similar failures.